MEDAN PRESS: NATIONAL IDENTITY FINDING PROCESS - Samri, Wannofri (Historia: Jurnal Pendidik dan Peneliti Sejarah, 2011)
Medan has grown really fast since the farm development in Deli, East Sumtara has begun in the end !9thÂ century. The development contributed a great impact to the development of the area sorounding East Sumtra. The cities surrounding the plantation had developed fast. Medan is one of the cities that develeloped as the impact of the wide development of the Ducthâ€™s colonial platation, followed by a great migration to that area from various nation. One of the most important development was Medan as a growing publishing center, both for book and mass media, such as magazine and news paper. The publishing figures came from various races, ethnics, and cultures, particularly from Aceh, Minangkabau, Java, Mandailing, and Batak. In addition, foreing publisher also existed, such as Europ, China, and India. Medan press development was good in the movements era, it considered as equal as Batavia, Surabaya, and Padang.